Ziff-Gulari-Barshad model with CO desorption under oscillating reactant pressure - Sinha I.; Mukherjee A.K. (My University, 2025)
We study the Ziff-Gulari-Barshad (ZGB) model subjected to periodic variation of reactant pressure, without desorption as well as at different desorption rates. Keeping the time period of oscillation fixed at a small value, Monte Carlo simulations are carried out at different amplitudes. With increase in the amplitude of oscillation, a transition occurs from the reactive state to the (partially) poisoned state. The reactant pressure oscillation is periodic cosine and symmetric about the ZGB discontinuous phase transition. Even for the model with no desorption, the numerical data for the fourth-order cumulant and the finite size scaling analysis suggest that the system does not undergo any phase transition but only a smooth crossover from the reactive to the poisoned state. © 2010 Elsevier B.V. All rights reserved.